Infectious diseases in the Tuscan detention setting: data from the Health Agency of Tuscany. (December 2016) - Sinisgalli, Ersilia; Silvestri, Caterina; Bravi, Stefano; Ceccherini, Vega; Tanini, Tommaso; Bonaccorsi, Guglielmo; Stasi, Cristina; Voller, Fabio
Highlights: The prison is one of the main reservoirs of infections. We evaluate the prevalence of infectious diseases among all the convicts of the Tuscany. Almost half of the subjects were Italian (49.8%) while the others (50.2%) were foreign. The most frequent infectious diseases were HCV and HBV (9.1% and 2.2%, respectively).